Intra- and intersystem interference in GNSS: Performance models and signal design - Enneking, Christoph (2020)
The European Galileo, the American Global Positioning System (GPS), and other global naviga- tion satellite systems (GNSSs) transmit direct-sequence spread spectrum (DSSS) signals from space, allowing receivers on Earth to compute their position, velocity, and time (PVT) based on the principle of pseudorange trilateration. However, as multiple satellites and systems transmit signals simultaneously within shared frequency bands, multiple access interference (MAI) in the form of intra- and intersystem interference can a ect signal processing at the receiver. To compute a pseudorange, the receiver must estimate synchronization parameters of the respective signal with high resolution. This synchronization is performed in a two-step approach, consisting of signal acquisition (detection) and fine parameter estimation. Most GNSSs rely on asynchronous direct-sequence code-division multiple access (DS-CDMA), assigning di erent pseudorandom noise (PRN) code to each satellite. This multiple access scheme involves a controlled level of MAI degrading acquisition and parameter estimation performance, which needs to be care- fully modeled before launching new signals or raising transmit power levels. The International Telecommunications Union (ITU) regulates that radio frequency compatibility (RFC) of systems, satellites and signals within the radionavigation frequency bands must be ensured, meaning that receiver performance must not be harmed significantly. Conventional receiver performance models are based on the spectral separation coe cient (SSC) between desired and interfering signal, and mostly rely on the idealization that GNSS signals are wide-sense stationary (WSS), circularly-symmetric Gaussian (CSG) random processes. In this work, we propose refined models for performance of coarse and fine estimation of synchronization parameters, taking into account the signals’ wide-sense cyclostationary (WSCS) property and their non-circularity. This is of particular interest in light of the recent signal design trend towards novel coarse/acquisition (C/A) signals with short PRN codes, which are especially vulnerable to MAI but very attractive for the group of mass-market GNSS-enabled electronic devices. Ultimately, our performance model enables the C/A signal designer to minimize the PRN code length while ensuring a given acquisition performance constraint. Moreover, with regard to RFC of an increasing number of navigation systems, satellites, and signals, our detailed models for interference e ects on user equipment will allow to make more e cient use of the available radio frequency spectrum.